Pengembangan E-Modul Kalfis Kinematika Menggunakan Aplikasi Flip Builder - Siwi Puji Astuti; Ria Asep Sumarni (Universitas Indraprasta PGRI Jakarta, 2022)
Making effective learning media is needed in the delivery of material, one of which is e-module. E-modules can assist in delivering material to students. The purpose of this research is to find out the e-module developed on Matlab-based kinematic physics using Flip Builder. The research was carried out in the Odd semester of 2021/2022. The method used in this research is the R&D method. The steps of the research development process from Borg and Gall. In this study, we have only arrived at the initial field testing step. The stages in this research are in the form of collecting material information in the form of teaching materials, planning, developing initial products, and ending with the provision of teaching materials ending with the Matlab kalfis e-module on kinematics material. The results of the learning module in the form of a flipbook that has been made using the flip builder can be used in bold learning on motion physics material, especially kinematics material because it looks attractive and can be developed further in learning. It is also very easy to use.